2023
DOI: 10.5194/amt-16-1211-2023
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of estimated liquid water content and scaling factor for warm clouds using radar–microwave radiometer synergy

Abstract: Abstract. Cloud radars are capable of providing continuous high-resolution observations of clouds and now offer new capabilities within fog layers thanks to the development of frequency-modulated continuous-wave 95 GHz cloud radars. These observations are related to the microphysical properties of clouds. Power law relations in the form of Z=a⋅LWCb are generally used to estimate liquid water content (LWC) profiles. The constants a and b from the power law relation vary with the cloud type and cloud characteris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Using neural net- work inversion, it provides vertical temperature and humidity profiles up to 2.5 km with a vertical resolution of 25 m up to 100 m high and 30 m above, as well as the liquid water path (LWP) over the whole layer. The synergy between both instruments was investigated for IOP 11 (Vishwakarma et al, 2023) and IOP 14 (Bell et al, 2022), by combining the LWP retrieved from the radiometer and the reflectivity from the BASTA radar in order to better estimate the vertical profile of LWC within the fog layer. However, we analyse here all the data collected during the SOFOG3D experiment, and we then use independant retrieval.…”
Section: Observationnal Sites and Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using neural net- work inversion, it provides vertical temperature and humidity profiles up to 2.5 km with a vertical resolution of 25 m up to 100 m high and 30 m above, as well as the liquid water path (LWP) over the whole layer. The synergy between both instruments was investigated for IOP 11 (Vishwakarma et al, 2023) and IOP 14 (Bell et al, 2022), by combining the LWP retrieved from the radiometer and the reflectivity from the BASTA radar in order to better estimate the vertical profile of LWC within the fog layer. However, we analyse here all the data collected during the SOFOG3D experiment, and we then use independant retrieval.…”
Section: Observationnal Sites and Instrumentationmentioning
confidence: 99%
“…The observation strategy combined vertical profiles derived from remote sensing instruments (microwave radiometer (MWR), Doppler cloud radar and Doppler lidars) and balloon-borne in-situ measurements of fog microphysics and thermodynamics. Bell et al (2022) and Vishwakarma et al (2023) combined cloud radar reflectivity with temperature and humidity profiles and LWP retrieved from MWR, to better estimate the vertical profile of LWC in the fog layer. They demonstrated that LWC retrieval is highly sensitive to the prescribed droplet concentration, and that agreement with in situ data is highly dependent on cloud-fog heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-based and spaceborne remote sensing techniques have been developed considerably over the past few decades. In remote sensing methods, power spectrum data measured by satellites and radars is used to invert to obtain cloud microphysics parameters [21][22][23][24][25][26][27][28][29][30]. Remote sensing methods have the advantage of detecting high-altitude clouds from a long distance [31,32].…”
Section: Introductionmentioning
confidence: 99%